The distributional impact of pension auto-enrolment - Claire Keane; Seamus O'Malley; Dora Tuda (The Economic and Social Research Institute (ESRI), 2021)
The Irish government plan to introduce pension auto-enrolment in the coming years. Subject to certain age and earnings thresholds, employees not covered by a supplementary pension will be auto enrolled into a retirement savings scheme. It is anticipated the initial employee contribution rate will be 1.5% rising to 6% after a number of years. While individuals can opt out of the scheme, this can only be done after an initial 6-month period. Those opting out of the scheme can receive a refund of their contributions after this 6-month period, however affordability issues may arise for some during these initial 6 months. In this paper we examine the distributional, poverty and inequality impacts of pension autoenrolment. We find that the largest negative impact will be felt in quintile 4, followed by quintile 3 - i.e. the middle income ranges. The bottom two income quintiles will see the smallest fall in disposable income. These results are driven by the fact that only 1% of family units in the lowest quintile and 7% in the second quintile will actually be affected by auto-enrolment due to lower employment incomes in these quintiles. There is no notable differing impact by gender, if anything women in lower income deciles face smaller losses - either because they do not work, do not earn enough to be auto-enrolled or are more likely to be covered already by an occupational pension due to their higher concentration in the public sector. There will be little impact on the at-risk-of-poverty rate. This is explained by the distributional impact findings whereby the largest negative impacts on disposable income were found for the upper income quintiles, for whom the 1.5% contribution rate examined is not sufficient to push them below the poverty line. These findings also hold for a higher 6% contribution rate.
Keywords: 330